Synthesis, identification, chiral separation and crystal structure of (3R,4R,7S,8S)-3,4,7,8-tetrachlorodecane and its stereoisomers - Valderhaug, Solveig; Paškanová, Natalie; Tůma, Jiří; Herciková, Jana; Eigner, Václav; Liu, Huiling; Gorovoy, Alexey; Johansen, Jon Eigill; Gautun, Odd Reidar (Heliyon, 2023)
Chlorinated paraffins (CPs) are a notoriously known class of compounds that stand amongst the most wide-spread persistent organic pollutants. Therefore, their reliable, repeatable, and reproducible quantitative analysis using well-defined reference standards is of utmost importance. In view of the increasing demand for constitutionally and stereochemically defined CP standards, we have synthesized a stereoisomeric mixture of 3,4,7,8-tetrachlorodecane. One stereoisomer - (3R,4R,7S,8S)-3,4,7,8-tetrachlorodecane was separated from the mixture, and enriched fractions of residual stereoisomers were achieved through crystallisation of the residual mother liquors. The molecular structure of the single isolated stereoisomer was confirmed through single-crystal X-ray crystallographic data. One fraction of 3,4,7,8-tetrachlorodecane stereoisomers was successfully separated on a chiral stationary phase using supercritical fluid chromatography hyphenated to mass spectrometry (column: Chiral ART Amylose-C; mobile phase: CO2/MeOH (96/4 v/v) with 0.1% diethylamine). The reported separation of stereoisomers is unprecedented in CP analysis so far.
Keywords: X-ray diffraction; Chlorinated paraffins; Amylose; Chiral supercritical fluid chromatography; Gas chromatography